2010
DOI: 10.1002/bjs.7174
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of laparoscopic Nissen (posterior total)versusToupet (posterior partial) fundoplication for gastro-oesophageal reflux disease

Abstract: LTF reduces postoperative dysphagia and dilatation for dysphagia compared with LNF. Reoperation rate and prevalence of gas-related symptoms were lower after LTF, with similar reflux control. These results provide level 1a support for the use of LTF as the posterior fundoplication of choice for GORD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
3
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(165 citation statements)
references
References 98 publications
10
135
3
17
Order By: Relevance
“…However, the Nissen procedure is often followed by troublesome effects. [1][2][3] To reduce the risk of these, partial fundoplications have been developed, and these modifications have been tested in randomized trials. 1;4-6 In the absence of late objective outcomes, some have questioned the durability of partial fundoplications, 7-10 even though longer term clinical outcomes from the trials actually support the application of anterior 180˚ and posterior 270˚ partial fundoplication techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Nissen procedure is often followed by troublesome effects. [1][2][3] To reduce the risk of these, partial fundoplications have been developed, and these modifications have been tested in randomized trials. 1;4-6 In the absence of late objective outcomes, some have questioned the durability of partial fundoplications, 7-10 even though longer term clinical outcomes from the trials actually support the application of anterior 180˚ and posterior 270˚ partial fundoplication techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Ten patients underwent endoscopic dilatation with safe and excellent results. Therefore, this treatment modality should be considered in patients with dysphagia and decrease in quality of life 6,16 .…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be no advantage of one over another in terms of costs, cost-effectiveness balances between longer duration of surgery in open fundoplication versus higher instrumental cost in laparoscopically surgery. 14,15 In adults, it has been established that, compared to Nissen fundoplication, laparoscopic partial fundoplication causes less dysphagia, gas bloating and redo surgeries [16][17][18] Similar to adult findings, pediatric observations suggested that total and partial fundoplication produce equivalent GER control in children 19 dysphagia may occur less frequently in partial versus total fundoplications. 20 These conclusions are however based on limited data and uncertainty remains with respect to the optimal fundoplication technique.…”
Section: Fundoplication Techniquesmentioning
confidence: 92%
“…19,21 Post operative dysphagia is the most common complication, occurring in 0-33% of patients in the first months after fundoplication. 16 Recently, Schneider et al retrospectively assessed a group of 288 children who underwent Nissen fundoplication. 21 In this study 24 percent of patients required lower esophageal dilation because of dysphagia.…”
Section: Efficacy and Safety Of Fundoplicationmentioning
confidence: 99%